Expression of SAP5 and SAP9 in Candida albicans biofilms: comparison of bloodstream isolates with isolates from other sources. (November 2013) - Joo, Min Young; Shin, Jong Hee; Jang, Hee-Chang; Song, Eun Song; Kee, Seung Jung; Shin, Myung Geun; Suh, Soon Pal; Ryang, Dong Wook
Abstract Secreted aspartic proteases (Sap), encoded by a family of 10 SAP genes, are key virulence determinants in Candida albicans. Although biofilm-associated bloodstream infections (BSIs) are frequently caused by C. albicans, SAP gene expression in C. albicans biofilms formed by BSI isolates has not been evaluated. We compared the expression of two SAP genes, SAP5 and SAP9, in C. albicans biofilms formed by BSI isolates with those formed by isolates from other body sites. Sixty-three C. albicans isolates were analyzed, comprising 35 BSI isolates and 28 from other sites. A denture-strip biofilm model was used, and expression of the two SAP genes was quantified by real-time RT-PCR during planktonic or biofilm growth. Mean SAP5 expression levels of the BSI isolates were 3.59-fold and 3.86-fold higher in 24-h and 48-h biofilms, respectively, than in planktonic cells. These results did not differ from those for isolates from other sites (2.71-fold and 2.8-fold for 24-h and 48-h biofilms, respectively). By contrast, mean SAP9 expression during biofilm formation was higher in BSI isolates (2.89-fold and 3.29-fold at 24 and 48 h, respectively) than in isolates from other sites (1.27-fold and 1.32-fold at 24 and 48 h, respectively; both, P < 0.001). These results show, for the first time, that both SAP5 and SAP9 are upregulated in C. albicans biofilms formed by BSI isolates, and that BSI isolates may have a greater capacity to express SAP9 under biofilm conditions than isolates from other sites.